Regulação assistencial e integralidade na assistência à saúde em Vitória-ES, sob a perspectiva da análise institucional - Siqueira, Márcia Portugal (2010)
This research deals with the access regulation to the health services workers network, public and private, contracted in order to guarantee the population access to the specialized assistance resources and its close relationship with the integrality guideline and principle, in the district of Vitoria-ES. It focus on integrality, in its individual clinical dimension, as axis, and the assistance access regulation, as cutout, on the macro-regulation scope in the public health systems, as well as the inter relation between these two dimensions. Seize the municipal different managements as object to examine the regulation rules and practices process of institutionalization and its effects in terms of provide integral attention to the district citizens. In this way this study searched to uncover the process of institutional change that took place in the Vitoria’s Municipal Health Secretariat throughout the twenty years of implantation of the Single Health System, through qualitative, exploratory, descriptive and analytical study, supported by documental sources and semi-structured interviews with the municipal health secretaries who managed during the period of 1989 to 2009. Anchored on the historical neo-institutionalism and on the concept of path dependency, the empirical data analyses demonstrate that the decisions made in the past impacted on the future trajectory of the health politics, either provoking incremental advances, or provoking embarrassments in the integral attention to the population and in the regulatory process. As results the indicators selected and elaborated point to relevant incremental advances towards integrality. The path dependency reveals itself in its most remarkable form in the managements in which were proposed institutional innovations whose conception brought as substrate political projects of different coalitions in the municipal management. These expressed themselves in the condition of municipal habilitation with the Health Ministry, in the attention model and organizational arrangements, in the assistance planning and in the State Health Secretariat informal relationships with the workers network. It reveals that, in a scenery of the private sector dependence, the Single Health System demands more effective instruments in order to firm with the workers network the state regulatory force. It still indicates the need for new investigations to enlarge the necessary knowledge to build capable means to measure the regulated integrality ... population access to the secondary and tertiary ... public health services systems.